(untitled) (Clinics, 2014)
OBJECTIVES: Primary hyperhidrosis usually affects the hands, armpits, feet and cranio-facial region. Sweating in other areas is common in secondary hyperhidrosis (after surgery or in specific clinical conditions). Oxybutynin has provided good results and is an alternative for treating hyperhidrosis at common sites. Our aim was to evaluate the efficacy of oxybutynin as a treatment for primary sweating at uncommon sites (e.g., the back and groin). METHODS: This retrospective study analyzed 20 patients (10 females) who received oxybutynin for primary focal hyperhidrosis at uncommon sites. The subjects were evaluated to determine quality of life before beginning oxybutynin and six weeks afterward and they were assigned grades (on a scale from 0 to 10) to measure their improvement at each site of excessive sweating after six weeks and at the last consult. RESULTS: The median follow-up time with oxybutynin was 385 days (133-1526 days). The most common sites were the back (n = 7) and groin (n = 5). After six weeks, the quality of life improved in 85% of the subjects. Dry mouth was very common and was reported by 16 patients, 12 of whom reported moderate/severe dry mouth. Five patients stopped treatment (two: unbearable dry mouth, two: excessive somnolence and one: palpitations). At the last visit, 80% of patients presented with moderate/great improvement at the main sites of sweating. CONCLUSION: After six weeks, more than 80% of the patients presented with improvements in their overall quality of life and at the most important site of sweating. Side effects were common (80% reported at least one side effect) and caused 25% of the patients to discontinue treatment. Oxybutynin is effective for treating bothersome hyperhidrosis, even at atypical locations and most patients cope well with the side effects.